(untitled) (Research, Society and Development, 2022)
Water has become a scarce environmental resource and the target of conflicts, whether due to the decreasing availability due to qualitative and quantitative factors, or due to the greater demand in production activities and public supply. In this sense, the objective was to analyze the availability and demand of water resources in Goiás, as well as the use of instruments for planning and management of water resources in the State. In the methodology, SEMAD, IBGE, ANA were consulted. A description of the hydrography of the region was conducted and data on availability and demands of Goiás and specifically for Water Resources Planning and Management Units (UPGRHs) were presented. The results showed that there is a growing demand for water, making it necessary to improve the mechanisms of planning and management of water resources in the state of Goiás.